(untitled) (Pesquisa Odontológica Brasileira, 2003)
The aim of this study was to evaluate standardized conduction velocity data for uninjured facial nerve and facial nerve repaired with autologous graft nerves and synthetic materials. An evaluation was made measuring the preoperative differences in the facial nerve conduction velocities on either side, and ascertaining the existence of a positive correlation between facial nerve conduction velocity and the number of axons regenerated postoperatively. In 17 rabbits, bilateral facial nerve motor action potentials were recorded pre- and postoperatively. The stimulation surface electrodes were placed on the auricular pavilion (facial nerve trunk) and the recording surface electrodes were placed on the quadratus labii inferior muscle. The facial nerves were isolated, transected and separated 10 mm apart. The gap between the two nerve ends was repaired with autologous nerve grafts and PTFE-e (polytetrafluoroethylene) or collagen tubes. The mean of maximal conduction velocity of the facial nerve was 41.10 m/s. After 15 days no nerve conduction was evoked in the evaluated group. For the period of 2 and 4 months the mean conduction velocity was approximately 50% of the normal value in the subgroups assessed. A significant correlation was observed between the conduction velocity and the number of regenerated axons. Noninvasive functional evaluation with surface electrodes can be useful for stimulating and recording muscle action potentials and for assessing the functional state of the facial nerve.